Molecular targets of Chinese herbs: a clinical study of metastatic colorectal cancer based on network pharmacology - Hongxu Zhu (Nature Portfolio, 2018)
Abstract Increasing evidence has shown that Chinese herbal medicine (CHM) has promising therapeutic effects in colorectal cancer (CRC); however, the active ingredients and potential targets remain unclear. In this study, we aimed to investigate the relative molecular targets of the Chinese herbs that have been found effective in treating metastatic CRC (mCRC) based on clinical data and network pharmacology. In multivariate analysis CHM resulted an independent prognostic factor. The hazard ratio was 0.103 (95% confidence interval = 0.064–0.164; P < 0.001). Compared with the non-CHM group, the median survival time of the CHM group was also improved (40 versus 12 months; P < 0.001). Eighteen out of 295 herbs showed significant correlation with survival results (P < 0.05). Bioinformatics analysis indicated that the 18 herbs realize anti-CRC activity mainly through suppressing the proliferative activity of ERBB2, peroxisome proliferator-activated receptor gamma, and retinoid X receptor, suppressing angiogenesis via inhibition of VEGFR and VEGFA expression, inhibiting the phosphatidylinositol-3-kinase/AKT1 signaling pathway directly through SRC and AKT1, and reducing tumor necrosis factor-induced inflammation.